Contributions of Siglo XXI Education to the professionalization of public servants (Revista Torreón Universitario, 2022)
The present study presents a critical assessment of the contribution of 21st century education to the study of the processes of professionalization of ethical and competent public servants. This is developed through the analysis of different types of education, education paradigms and trends in education, in particular the approach to competences and types of competences, both general competences and specific competences with which public servants must be trained so that they can contribute to the transformation of the public administration for which they work in particular and for their society in general. In this work special emphasis is placed on the ethical aspect and on the critical aspect that the education of the 21st century. The document is structured in the following sections: introduction, material and methods, analysis of results, conclusions and bibliographic references.
Keywords: skills; 21st century education; public servants; proffesionalization